AMPylation: Something Old is New Again - Woolery, Andrew R.; Luong, Phi; Broberg, Christopher A.; Orth, Kim (Frontiers in Microbiology, 2010)
The post-translational modification AMPylation is emerging as a significant regulatory mechanism in both prokaryotic and eukaryotic biology. This process involves the covalent addition of an adenosine monophosphate to a protein resulting in a modified protein with altered activity. Proteins capable of catalyzing AMPylation, termed AMPylators, are comparable to kinases in that they both hydrolyze ATP and reversibly transfer a part of this primary metabolite to a hydroxyl side chain of the protein substrate. To date, only four AMPylators have been characterized, though many more potential candidates have been identified through amino acid sequence analysis and preliminary in vitro studies. This modification was first discovered over 40 years ago by Earl Stadtman and colleagues through the modification of glutamine synthetase by adenylyl transferase; however research into this mechanism has only just been reenergized by the studies on bacterial effectors. New AMPylators were revealed due to the discovery that a bacterial effector having a conserved Fic domain transfers an AMP group to protein substrates Current research focuses on identifying and characterizing various types of AMPylators homologous to Fic domains and adenylyl transferase domains and their respective substrates. While all AMPylators characterized thus far are bacterial proteins, the conservation of the Fic domain in eukaryotic organisms suggests that AMPylation is omnipresent in various forms of life and has significant impact on a wide range of regulatory processes.